PENGEMBANGAN E-MODUL KIMIA BERBASIS SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) UNTUK SISWA SMAN 1 KECAMATAN PAYAKUMBUH - Safitri, Rahmi; Sari, Maya (Journal of Chemistry Education and Integration, 2022)
AbstractThe problem behind this research is the unavailability of teaching materials that are effective and attract students' interest in learning. The teaching materials used during the chemistry learning process only utilize textbooks provided in the library and use student worksheets. This causes students to have difficulty understanding the concepts of chemistry, because textbooks tend to be monotonous and difficult to understand, moreover most of the material in chemistry learning is abstract so it needs a better explanation. Meanwhile, teachers have not developed interesting and easy-to-understand teaching materials due to time constraints. Based on this, the researchers conducted research on the development of SETS (Science, Environment, Technology, and Society)-Based Chemistry E-Modules for Class XI Students on petroleum materials. This research uses 4-D research (define, design, develop, and disseminate). To find out the validity or practicality of an e-module, validity and practicality tests are carried out. The results showed that the validation of the SETS-based chemical e-module that had been designed was very valid with a percentage of 96.8%, and the practicality results were very practical with a percentage of 89.0%. Keywords : Development, E-Module, SETS Approach